Insuficiência adrenal na sepse em pacientes pediátricos - Motta, Márcia Taschetto (2014)
Adrenal insufficiency is common in pediatric patients with septic shock, but remains underdiagnosed in the early stages of sepsis. The early recognition of the factors representing risk for septic shock is crucial, since no control of them can increase the risk of death. This study aimed to verify the occurrence of adrenal insufficiency and describe the clinical and initial laboratory findings in children hospitalized for sepsis. This was a descriptive study, which included children admitted to the Pediatric Intensive Care Unit of the University Hospital of Santa Maria, in the period from March to October, 2013. We studied five patients with sepsis. For adrenal insufficiency diagnoses we performed the ACTH stimulation test. A positive test was considered when an increment on the cortisol level equal or less 9 μg/dL occurred. Five children were analyzed, 80 % were male with a mean age of 7.3 years (±4.2). The initial laboratorial findings confirmed the presence of sepsis. Adrenal insufficiency was diagnosed in 2 of 5 patients studied, representing 40 %. Only one patient (20%) required mechanical ventilation. There was no progression to septic shock in any of the patients studied. All patients were discharges from hospital. We concluded that adrenal insufficiency may be present in pediatric patients with sepsis, in its earliest stages.